IMPLEMENTASI RENCANA BIDANG PENGAWASAN DAN IMPLIKASINYA TERHADAP AKUNTABILITAS SATUAN KERJA PERANGKAT DAERAH - Ita Marthawati Andyni, Mrs. (FIA UB, 2012)
This study tries to describe and analyze (1) the implementation of the audit planning ofnthe Inspectorate of Malang Regency; (2) the implications of the implementation of audit planning done by the Inspectorate of Malang Regency to the SKPDsâ accountability; and (3) the factors that support and hinder the implementation of audit planning on the Inspectorate of Malang Regency. This study uses qualitative research methods with a case study approach. The results of this study show that: first, the implementation of the audit planning for regular inspection activities in the Inspectorate of Malang Regency still have many weaknesses as there are some inhibiting factors even though the arrangement of the audit planning process has been performed well; second, although the implementation of the audit planning for regular inspection activities at the Inspectorate of Malang Regency could not have been performed, but SKPDsâ as the auditee still have the benefits even the investigation still has positive implications to the accountability of the SKPDsâ, eventhough it is not in the optimal degree; and third, the supporting factors of the implementation of the audit planning for regular inspection activities in the Inspectorate of Malang Regency consist of: the position of the Inspectorate as an internal controller, the availability of budget for the controlling activities, the experienced controlling apparatus, the availability of facilities and infrastructures and positive responses from the auditee. While the inhibiting factors consist of: Inspectorate is not an independent institution, the realisation of budget is often late, the facilities and infrastructures are limited, the quality of the controlling apparatus hasnât been equal, the unbalanced ratio between the number of controlling apparatus with the number of the auditor, there hasnât been a functional position, there are some overlappings with other controlling activities, there is time limitation in doing control, the complexity of the controlling findings and the lack of responses from the auditor.